WNT4, RSPO1, and FOXL2 in Sex Development - Biason-Lauber, Anna (Seminars in Reproductive Medicine, 2012)
The idea that the female sexual development happens by default was born in the middle of the last century after Jost performed his innovative experiments to study the bases of differentiation of the reproductive tract and found that the female reproductive tract develops even in the absence of any gonad. The term default (passive) attributed to the whole female developmental pathway, therefore, established itself, even if it was not originally so intended. However, recent developments have demonstrated that ovarian development is an active process. Wingless type MMTV integration site family, member 4 (WNT4), one of a few factors with a demonstrated function in the ovarian-determination pathway, has been found to be involved in sexual differentiation by suppressing male sexual differentiation, promoting Müllerian duct differentiation, and maintaining oocyte health. WNT4 expression in the ovary seems to be regulated by R-spondin 1 (RSPO1), a thrombospondin family member protein. The role and interactions of WNT4, RSPO1, and other factors such as forkhead transcription factor 2 in ovarian development and function will be discussed.
Keywords: ovarian differentiation; WNT4; RSPO1